2017
DOI: 10.1111/cns.12702
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoginsenoside‐F11 attenuates cerebral ischemic injury by alleviating autophagic/lysosomal defects

Abstract: These findings indicate that the autophagic flux is impaired in a rat model of pMCAO, and that PF11 exerts an excellent protective effect against ischemic stroke by alleviating autophagic/lysosomal defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 53 publications
0
16
0
Order By: Relevance
“…In a 2vessel occlusion (2-VO) ischemic stroke model, treatment with chloroquine (CQ) does not further change the LC3-II levels, suggesting that ALP is impaired [8]. In our latest study, impaired ALP function is also observed at 24 h in a model of permanent cerebral ischemia [9]. Additionally, lysosomal dysfunction, as reflected by cytosolic acidification and rupture/ permeabilization, is detected after ischemic insult [10][11][12].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…In a 2vessel occlusion (2-VO) ischemic stroke model, treatment with chloroquine (CQ) does not further change the LC3-II levels, suggesting that ALP is impaired [8]. In our latest study, impaired ALP function is also observed at 24 h in a model of permanent cerebral ischemia [9]. Additionally, lysosomal dysfunction, as reflected by cytosolic acidification and rupture/ permeabilization, is detected after ischemic insult [10][11][12].…”
Section: Introductionmentioning
confidence: 79%
“…Mounting evidence strongly indicates that ALP is induced in multiple ischemic stroke models as reflected by the accumulation of autophagosomes and activation of lysosomal function [1,2,6,7]. However, it is noteworthy that ischemic injury can trigger a defect in ALP by causing lysosomal dysfunction, thus resulting in the abnormal accumulation of autophagosomes and substrates [8][9][10][11][12]. In a 2vessel occlusion (2-VO) ischemic stroke model, treatment with chloroquine (CQ) does not further change the LC3-II levels, suggesting that ALP is impaired [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the benefits of autophagy in acute ischemic brains have been documented, few compounds were known to rescue ischemic brain injury by targeting autophagy . Uro‐A activates autophagy in several types of cell, yet it has been undetermined whether Uro‐A also activates autophagy in ischemic neuronal cells and mice brain.…”
Section: Discussionmentioning
confidence: 99%
“…It was capable of improving lysosomal function and lysosome/autophagosome fusion following pMCAO. This change was reversed by the lysosomal inhibitor chloroquine, which, in turn reversed improvement in ischemic outcome and the antiapoptotic effect [ 115 ].…”
Section: Pharmacological Potential Of Active Ginseng Constituents In mentioning
confidence: 99%